Multisynaptic Projections from the Amygdala to the Ventral Premotor Cortex in Macaque Monkeys: Anatomical Substrate for Feeding Behavior - Ishida, Hiroaki; Inoue, Ken-ichi; Takada, Masahiko (Frontiers in Neuroanatomy, 2018)
The amygdala codes the visual-gustatory/somatosensory valence for feeding behavior. On the other hand, the ventral premotor cortex (PMv) plays a central role in reaching and grasping movements prerequisite for feeding behavior. This implies that object valence signals derived from the amygdala may be crucial for feeding-related motor actions exerted by PMv. However, since no direct connectivity between the amygdala and PMv has been reported, the structural basis of their functional interactions still remains elusive. In the present study, we employed retrograde transneuronal labeling with rabies virus to identify the amygdalar origin and possible route of multisynaptic projections to PMv in macaque monkeys. Histological analysis of the distribution pattern of labeled neurons has found that PMv receives disynaptic input primarily from the basal nucleus, especially from its intermediate subdivision. It has also been revealed that the medial (e.g., the cingulate motor areas) and lateral (e.g., the insular cortices) cortical areas, and the cholinergic cell group 4 in the basal forebrain probably mediate the projections from the amygdala to PMv. Such multisynaptic pathways might represent amygdalar influences on PMv functions for feeding behavior.